2021
DOI: 10.3389/fendo.2020.582670
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Intermittent Hypobaric Hypoxia Enhances Bone Fracture Healing

Abstract: The effect of chronic intermittent hypobaric hypoxia (CIHH) on bone fracture healing is not elucidated. The present study aimed to investigate the role of CIHH on bone fracture healing and the mechanism. The Sprague-Dawley rats were randomly divided into the CIHH group and control group and monitored for 2, 4, or 8 weeks after femoral fracture surgery. Bone healing efficiency was significantly increased in the CIHH group as evidenced by higher high-density bone volume fractions, higher bone mineral density, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…Bone marrow stem cells can recruit circulating bone marrow‐derived stem cells and endothelial progenitor cells to the injury site through HIF‐1α‐dependent SDF‐1 and its receptor CXC chemokine receptor 4 (CXCR4) 11,36,48 . Through upregulated the HIF‐1α/SDF‐1/CXCR4 axis using exogenous SDF‐1, confirmed that the rise in SDF‐1 is coupled with increased HIF‐1α and CXCR4 expression and that the upregulated HIF‐1α/SDF‐1/CXCR4 axis can also reduce apoptosis and promote cell self‐renewal 13 .…”
Section: The Possible Mechanism By Which Hif‐1α Promotes Bone Regener...mentioning
confidence: 90%
See 2 more Smart Citations
“…Bone marrow stem cells can recruit circulating bone marrow‐derived stem cells and endothelial progenitor cells to the injury site through HIF‐1α‐dependent SDF‐1 and its receptor CXC chemokine receptor 4 (CXCR4) 11,36,48 . Through upregulated the HIF‐1α/SDF‐1/CXCR4 axis using exogenous SDF‐1, confirmed that the rise in SDF‐1 is coupled with increased HIF‐1α and CXCR4 expression and that the upregulated HIF‐1α/SDF‐1/CXCR4 axis can also reduce apoptosis and promote cell self‐renewal 13 .…”
Section: The Possible Mechanism By Which Hif‐1α Promotes Bone Regener...mentioning
confidence: 90%
“…46 A rat fracture model treated with intermittent hypoxia and found that VEGF expression in the fracture site was significantly increased compared with that in the control group at weeks 2 and 4, while platelet endothelial cell adhesion molecule-1 (PECAM-1; CD31), a vessel-specific marker, was also specifically increased, suggesting that intermittent hypoxia promoted local vascular regeneration by upregulating the HIF-1α-VEGF axis. 11 As an upstream regulator of the angiogenic response, HIF-1α can increase angiogenesis by activating other pathways in addition to VEGF. There is a complex tandem between HIF-1α and bFGF, and HIF-1α-bFGF forms an autocrine loop under hypoxic conditions, suggesting the existence of an amplification pathway that mediates the survival of endothelial cells and neovascularization sprouting.…”
Section: Promoting Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Although a few studies report that chronic intermittent hypoxia in OSA brings a negative effect on bone formation, some other studies find that chronic intermittent hypoxia does no harm to the bone and it can even enhance bone fracture healing. 43 , 44 It is critical to define key characteristics of CIH protocol, including the exposure periods per day, the duration of hypoxic episodes and hypoxia levels. Severe/chronic CIH protocols tend to be pathogenic, while beneficial effects are more likely to result from modest/acute CIH exposures.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, blood flow drops immediately, leading to regional hypoxia. However, in part, hypoxia is also involved in promoting fracture healing [ 13 ]. Therefore, hypoxia plays a particular role in bone homeostasis under physiological and pathological aspects, and exploring and clarifying the underlying mechanism is necessary.…”
Section: Introductionmentioning
confidence: 99%